STUDY THE EXPRESSION OF IL-22 GENE IN AUTOIMMUNE HYPOTHYROIDISM IN IRAQ - A.A. H.Yassin; A. A. Al-Kazaz; A. M. Rahmah; T. Y. Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to assess expression of IL-22 gene in patients with newly diagnosed autoantibodies against the thyroid antigens; anti-thyroglobulin (anti-TG), and anti-thyroid peroxidase (anti-TPO) in comparison with patients previously diagnosed and treated for autoimmune hypothyroidism as well as healthy control individuals. Twenty-eight patients with positive anti-TG and/or anti-TPO were enrolled in this study along with twelve age- and gender-matched healthy controls. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to assess gene expression and fold change among the study groups. Results revealed anti-TG concentration ranges of 134.3 to 2998.9 IU/mL and anti-TPO concentration ranges of 41.6 to 1018.4 IU/mL in patients while control group individuals were negative for these autoantibodies. The mean fold change of IL-22 expression (2-∆∆Ct) was the highest in newly diagnosed patients compared to patients on treatment for autoimmune hypothyroidism and healthy controls indicating the potential role of IL-22 in the early stages of the disease and its contribution in immune imbalance.